1966
DOI: 10.1111/j.1939-0025.1966.tb02410.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of learning problems seen in five child clinics.

Abstract: To what extent do clinical record data vary as a function of differences in institutional data collection practices? Fifty records of learning problems, ten of which were gathered in each of five clinics, were transcribed into computer‐acceptable form using a generalized information processing system, the Psychiatric Case History Event System, so that comparative studies of their structure and content could be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1967
1967
1968
1968

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Comparative studies of learning problems in latency age boys: (Eiduson, Johnson, and Rottenberg, 1966) Recent studies of children with learning problems identified a number of learning syndromes with specific clinical and psychodynamic features. These syndromes were established by investigators working in various psychiatric facilities.…”
mentioning
confidence: 99%
“…Comparative studies of learning problems in latency age boys: (Eiduson, Johnson, and Rottenberg, 1966) Recent studies of children with learning problems identified a number of learning syndromes with specific clinical and psychodynamic features. These syndromes were established by investigators working in various psychiatric facilities.…”
mentioning
confidence: 99%